An exanthematic disease epidemic associated with coxsackievirus B3 infection in a day care center Epidemia de doença exantemática associada à infecção causada por coxsackievírus B3 em uma creche - Regina C. Moreira; Silvana B. Castrignano; Rita de C. C. Carmona; Filumena M. S. Gomes; Sueli G. Saes; Rosely S Oliveira; Denise F. C. Souza; Sueko Takimoto; Marisa C. L. Costa; Eliseu Alves Waldman (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
An epidemic of exanthematic illness in a day care center is described. Ten children aged 7 to 13 months were affected by the illness. The exanthem was characterized by nonconfluent macular or maculopapular lesions that appeared on the face, body and limbs. Fifty percent of the infected children had fever of up to 39ºC at the beginning of the disease. Coxsackievirus B3 (CB3) was isolated from the stool of one ill child. Paired serum samples were obtained from eight ill children and six of them presented seroconversion to CB3. Antibodies to CB3 were detected at titers higher than 16 in a single serum sample collected from the other two patients. Neutralizing antibodies to CB3 were detected in 71.0% of the contact children. É descrita uma epidemia de doença exantemática em uma creche, acometendo 10 crianças de 7 a 13 meses de idade. O quadro exantemático caracterizou-se por lesões máculo ou maculopapulares não confluentes, que atingiam a face, tronco e pernas. 50% das crianças infectadas apresentaram febre de até 39ºC, no início da doença. Foi isolado das fezes de uma criança doente o coxsackievírus B3 (CB3). Foram examinados soros pareados de 8 das 10 crianças doentes e em 6 delas demonstrou-se soroconversão para CB3. Duas crianças que apresentaram sintomatologia e que tiveram amostras de sangue colhidas somente 7 meses após a epidemia, apresentaram anticorpos específicos contra o CB3, em títulos superiores a 16. Entre os contatos das crianças doentes, verificou-se que 71,0% do total apresentaram anticorpos neutralizantes específicos contra o CB3.